Determination of Drying Kinetics for Nagpur Orange Fruit (Citrus sinensis-L) Using a High-Efficiency Hot Air Electrical Dryer: An Experimental Investigation - Prashant M. Rewatkar; Sandip S. Jawre; Sanket R. Choudhari (Theory and Applications of Engineering Research Vol. 2, 2024)
This study focuses on the experimental investigation and theoretical comparison of drying kinetics for Nagpur orange fruit in a hot-air electrical dryer. Given the high perishability of orange fruit, immediate consumption or processing is crucial post-harvest. Dehydration emerges as a practical preservation method, prompting an exploration of thin layer drying characteristics under varying conditions such as drying air temperatures, relative humidity, and air velocities across different moisture contents. The research employs thin layer models, specifically Wang and Singh, Page, and Henderson, to compare theoretical predictions with experimental findings. Understanding drying kinetics proves essential for pinpointing precise drying times and optimal air flow velocities corresponding to different moisture levels. The drying operation is executed at velocities of 1 m/s and 1.25 m/s for temperatures of 55°C, 65°C, and 75°C. Results indicate that drying temperature significantly influences moisture removal, whereas velocity exerts the least impact. The drying rate increases with increasing temperature and diminishes over time. The statistical correlation of experimental data through drying characteristic curve plotting reveals that Wang and Singh’s model outperforms others in elucidating the drying behavior of Nagpur orange fruit (R²=0.9711). This comprehensive analysis enhances our understanding of the intricate interplay between drying parameters, contributing valuable insights for optimal drying conditions and efficient preservation.